A review on performance of polyester fibers in alkaline and cementitious composites environments. (30th April 2020) - Rostami, Rouhollah; Zarrebini, Mohammad; Mandegari, Mansoor; Mostofinejad, Davood; Abtahi, Sayyed Mahdi
Highlights: Fiber reinforcement concrete (FRC) has been very attractive in civil engineering. Concrete is highly alkaline which can readily impart different degradation level to fibers. Performance of polyester fibers in alkaline and cementitious composites environments have been studied. Abstract: The performance of various fibers as a reinforcement in cementitious composites has been studied by many researchers. The point of paramount importance is that cement-based materials are highly alkaline environment. Polyethylene terephthalate (PET) as a man-made fibers in alkaline environment can be subjected to degradation. The available information on stability of PET fibers in cement-based materials is insufficient and inconsistent. Although some researches have rejected the use of these fibers as a suitable reinforcing element in cementitious composites, there are others that have positively advocated the use of such fibers in concretes. This review paper aims to thoroughly investigate the performance of PET fibers in alkaline environment of cementitious composites. Thus chemical degradation of PET fibers and their subsequent behavior when used in alkaline environment of cementitious composites is well documented. The paper encompasses an up to date critical evaluation of the so far conducted research works and additional future research requirements in this field. The overall conclusion that can be drawn is related to the fact that, despite degradation of the added PET fibers, in most applications properties of the cementitious composites can be enhanced. This phenomenon can be attributed to improvement resulted from other properties of the PET fibers in alkaline environment.